ENFORCEABILITY OF MEDIATION SETTLEMENT AGREEMENTS: UKRAINIAN PERSPECTIVE IN THE LIGHT OF CURENT TRENDS - Kateryna Manetska; Olena Levchyshyna (International Comparative Jurisprudence, 2020)
In the light of active discussions concerning the recent introduction of the Singapore Convention, the issue of enforcement of mediation settlement agreements has become more topical. The following article is devoted to the study of international experience in the enforceability of agreements resulting from mediation, and the current Ukrainian situation in this context. While most European countries provide effective mechanisms of enforcement, in Ukraine this issue remains unresolved. Due to the lack of a special legislative act devoted to mediation, there is no explicit approach to the mode of enforcement. Therefore, the authors study ongoing legislative works on the Draft Law of Ukraine on Mediation and the impact of the Singapore Convention alongside possible modes of implementation.